A methods engineering study on Synthetic World Corporation - Gonzales, Edello; Quirapas, Marden Edward (Diliman, Quezon City College of Engineering, 2003)
Synthetic World Corporation (SWC) is a manufacturer, designer and distributor of high quality plastic products made from PVC, HDPE, LDPE and PP, using injection and blow moulding processes. Within a span of about thirteen (13) years, SWC has attained considerable growth and stability. It is one of the leading manufacturers, makers and designers of high quality food, drug, cosmetics, lubricants and promotional plastic containers in the Philippines. Data were gathered through interviews and actual observations in the workplace. These data were documented using tools and concepts in Methods Engineering. The group identified all problem areas using the Stream Diagnostic Chart and Ishikawa Diagrams. Eight core problems were determined and these were : (1) Allocation of space to defective machines which should have been used for Finished Goods Storage, (2) No immediate policy on unused stocks disposal, (3) No Standard mixing procedure leading to the spillage of raw materials (4) No standard procedure on colorant portioning (5) Relatively low elevation of holding bin (6) Material loss in grinding machine holding bin/drum (7) Inefficiency of the existing printing layout and (8) Insufficient material handling equipment. These problems were each provided with alternative solutions. The alternatives were assessed against specific objectives appropriate for each. The evaluations showed that the better solution for insufficiency of material handling equipment is to develop a standard transport schedule. Designing a new bin that will lessen the material spillage can solve the problem on inefficient holding bin for grinding. The issue regarding the non-moving stocks, inefficiency printing layout and allocation of defective machines should be addressed by rearranging the layout to attain at least 100 percent space utilization. Developing a standard procedure for mixing and colorant portioning will also help solve the issues. These improvements will result in increased productivity and reduce delays in the production process. Implementation plans were provided. Recommendations were given for the company to consider in improving their current system.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Synthetic World Corporation; Plastics industry and trade; Systems analysis